Analysis of Financial Ratios for Predicting Bankruptcy in SMEs Listed on PEFINDO25 - Vitalia Fina Carla Rettobjaan (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2020)
This study aims to analyze the Financial Ratio for Predicting Bankruptcy. The sample used in this study are SMEs according PEFINDO25 period 2013 to 2017. The independent variables in this study is liquidity, profitability, debt structure, solvency and activity ratio; and control variables is size and age, as well as the dependent variable is bankruptcy. The amount of sample in this study 32 companies PEFINDO25 by using purposive sampling. The method of data analysis is done by using logistic regression with SPSS version 23. The result of this research showed that liquidity, profitability and age has significant negative effect on bankruptcy. Debt structure has significant positive effect on bankruptcy. While solvency, activity ratio and size does not significantly effect on bankruptcy